Peningkatan Rumah Desa Sehat sebagai Pusat Konvergensi dalam Percepatan Penanganan Stunting di Kabupaten Mandailing Natal - Irman Puansah; Darman Syah Pulungan; Rahmat Haris Saputra Harahap; Wina Sifa Hani Gultom (Pusat Riset dan Inovasi Nasional, 2026)
The high prevalence of stunting in Mandailing Natal Regency, despite showing a declining trend in recent years, is still above the national target, thus requiring acceleration efforts through a convergence approach at the village level. This study aims to analyze the effectiveness of the implementation of Healthy Village Houses (RDS) as a center for the convergence of stunting handling acceleration, identify supporting and inhibiting factors, and formulate strategies to strengthen the RDS institution. The research used a qualitative descriptive method with data collection techniques including in-depth interviews, participatory observation, and documentation studies involving local government, village government, health workers, Human Development Cadres (KPM), and posyandu cadres. Data analysis was performed using the Miles & Huberman interactive model through the stages of data condensation, data presentation, and drawing conclusions. The results show that RDS functions as a multisectoral coordination platform, a nutrition education center, as well as a space for integrating various health services such as integrated posyandu and child growth and development monitoring. However, its implementation has not been optimal due to limited budget allocation, low human resource capacity, weak institutional documentation, and low community participation. The study concludes that strengthening RDS requires specific budget support, clear institutional regulations, capacity building for cadres, more intensive integration with health centers, and improving community nutrition literacy. Optimizing RDS is crucial to accelerate the reduction of stunting rates and strengthen village-based health governance.